Microfluidic Assays: A Precise Microfluidic Assay in Single‐Cell Profile for Screening of Transient Receptor Potential Channel Modulators (Adv. Sci. 11/2020). Issue 11 (10th June 2020) - Ai, Xiaoni; Wu, Yang; Lu, Wenbo; Zhang, Xinran; Zhao, Lin; Tu, Pengfei; Wang, KeWei; Jiang, Yong
Abstract : In article number 2000111, Pengfei Tu, KeWei Wang, Yong Jiang, and co‐workers develop a precise microfluidic assay in single‐cell profile for screening of transient receptor potential (TRP) channel modulators. The single‐cell‐based screening strategy dramatically reduces false‐positive/negative results from 76.2% to 4.8% due to full consideration of single‐cell heterogeneity. Four novel coumarin derivatives are cherry‐picked to potently inhibit TRP channels. One of the positive hits, B‐304, reverses TRPA1‐mediated inflammatory pain in vivo.